The Effect of Career Development and Performance Awards on Employee Loyalty with Job Satisfactionas an Intervening VariableAt the Regional Secretariat of Pekalongan Regency - Aji, Anom Sanyoto; Umaina, Faradian (Proceeding of The International Conference on Business and Economics, 2026)
This study aims to examine the influence of career development and work environment on employee performance through work awards as an intervening variable in the regional secretariat of Pekalongan Regency This research was conducted by a survey method of employees with job satisfaction as an intervening variable in the regional secretariat of Pekalongan Regency The sampling technique used in this study was a census of 56 respondents. Data collection through the dissemination of questionnaires, data analysis in this study uses SmartPLS The analysis used is Outer Model Test, Validity Test, Feasibility Test, Structural Model Test, Hypothesis Test. The results of the study showed that Career Development and work awards have a positive and significant effect on Job Satisfaction, Career Development and Work awards have a positive and significant effect on Employee Performance, Career Development variables and Work awards have a positive and significant effect on Employee Performance through Job Satisfaction.